Padrões macroevolutivos do tamanho do cérebro e tipos de ninhos em passeriformes - Leite, Abraão de Barros (2020)
Birds and mammals have increased cognitive abilities and selective forces favoring complex behavioral skills are considered important drivers of brain evolution. A tractable way to infer about evolutionary pathways shaping brain complexity is to compare brain sizes between groups of organisms with different behavioral and ecological characteristics. The construction of closed nests is one of the most remarkable abilities of birds, but its relationships with brain size remains unexplored. Here we use data from 538 bird species to test whether species that build closed nests have larger brains compared to those that build open nests. We also controlled to the effects of body size and migration, both known to affect brain size. Through a Bayesian approach with phylogenetic control, we reveal that the construction of closed nests is not correlated to disproportionally enlarged brains, thus contradicting the current thought that the architecture of closed nests is more complex in relation to open nests. This lack of significance suggests the existence of variations in the complexity of both closed nests and open nests, in addition to the effects of negative allometry that occurred throughout the evolution of the passerines. Although our results do not show a nest type effect, the idea that, on average, closed nests may be associated with larger brains may not be readily ruled out. Thus, once a treatable amount of brain size data becomes available, analyses should focus, for example, on specific families that have as many nest-independent transitions as possible.